The Nazi Conspiracy : the secret plot to kill Roosevelt, Stalin, and Churchill - Meltzer, Brad; Mensch, Josh (New York : Flatiron Books, 2023)
"From the New York Times bestselling authors of The First Conspiracy and The Lincoln Conspiracy, The Nazi Conspiracy tells the little-known true story of a Nazi plot to kill FDR, Joseph Stalin, and Winston Churchill at the height of the second World War. In 1943, as the war against Nazi Germany raged abroad, President Franklin Roosevelt wanted one thing: a face-to-face meeting with his allies Joseph Stalin and Winston Churchill. This meeting of the Big Three in Tehran, Iran, would decide some of the most crucial strategic details of the war. Yet when the Nazis found out about the meeting, their own secret plan took shape-an assassination plot that would've changed history. A true story filled with daring rescues, body doubles, and political intrigue, The Nazi Conspiracy details FDR's pivotal meeting in Tehran, and the deadly Nazi plot against the heads of state of the three major Allied powers who attended it. With all the hallmarks of a Brad Meltzer and Josh Mensch page-turner, The Nazi Conspiracy examines the great political minds of the 20th century, exploring the early years of the war in gripping detail. This meeting of The Big Three changed the course of World War II. Here's the inside story of how it all almost went terribly wrong"--
Maps on endpapers.
Includes bibliographical references (pages 341-379) and index.
Keywords: Roosevelt, Franklin D. -- 1882-1945.; Stalin, Joseph, -- 1878-1953.; Churchill, Winston, -- 1874-1965.; Operation Long Jump, 1943.; World War, 1939-1945 -- Secret service -- Germany; Conspiracies -- Iran -- Tehran -- History -- 20th century; Conspiracies -- Germany -- History -- 20th century